The Influence of Transparency and Village Financial Accountability on Village Fund Management in Bajo Village, Liang District - Novianti Helman; Yuwin Ali; Dharmawaty S. Makur (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Transparent and accountable village fund management represents a fundamental principle of good village governance and plays an important role in supporting effective local development. A quantitative approach was employed to examine the influence of transparency and village financial accountability on village fund management in Bajo Village, Liang District. Data were collected through questionnaires distributed to 45 respondents consisting of village officials, members of the Village Consultative Body (BPD), community leaders, and community representatives. Data analysis was conducted using multiple linear regression supported by validity, reliability, and classical assumption tests. The findings reveal that transparency has a positive and significant effect on village fund management, with a significance value of 0.000 and a regression coefficient of 0.451. Financial accountability also demonstrates a positive and significant effect, with a significance value of 0.001 and a regression coefficient of 0.372. Simultaneously, transparency and accountability significantly influence village fund management, as indicated by a significance value of 0.000 and a coefficient of determination (R²) of 0.621. These results indicate that greater information disclosure, timely reporting, and stronger financial responsibility contribute to more effective, efficient, and accountable village fund management practices. Nevertheless, limitations related to public access to financial information and the administrative capacity of village officials remain important challenges that require continuous improvement to strengthen governance quality and ensure sustainable village development.